Fish Marketing in Pondicherry: A Study of Marketing Costs and Margin - Ibrahim, P.; Vallathan, M. (Indian Journal of Marketing, 2006)
Marketing plays a very important role in economic development as it stimulates production, avoids unnecessary fluctuations in output and prices and reduces costs of production. However, for these benefits to occur marketing system and marketing technology have to keep pace with the production technology and socio economic development of the country. The experience of many countries suggests that in the absence of an efficient marketing system any strategy for agricultural development cannot go very far to stimulate production.